2021
DOI: 10.1002/csr.2196
|View full text |Cite
|
Sign up to set email alerts
|

Does board gender diversity improve the welfare of lesbian, gay, bisexual, and transgender employees?

Abstract: This paper focuses on two of the highly debated social issues corporations that are pressured to address—gender equality and workplace discrimination. Countries around the world mandate gender quotas on corporate boards to facilitate firms in addressing the issue of gender equality and anti‐discrimination legislations to address workplace discrimination. Gender diversity on the corporate boards can sway the board toward addressing more to the society and the environment—the external stakeholders of the firm. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 66 publications
1
6
0
Order By: Relevance
“…In addition, as women are more concerned with ethical conduct (Ford & Richardson, 1994), gender diversity can lead to better social performance. (Veltri et al, 2021; Cucari et al, 2018; Kassinis et al, 2016; Hafsi & Turgut, 2013; Yasser et al, 2017; Xie et al, 2020; Orazanlin and Baydauletov, 2020; Amorelli and Garcia‐Sanchez, 2021; Kyaw et al, 2022; Buertey, 2021; Cuadrado‐Ballesteros et al, 2017; Bernardi et al, 2011; Liu et al, 2020; McGuinness et al, 2017) and better CSR disclosure (Cabeza‐García et al, 2018; Nekhili et al., 2017; Rao & Tilt, 2016).…”
Section: Review Of Related Literaturesmentioning
confidence: 99%
“…In addition, as women are more concerned with ethical conduct (Ford & Richardson, 1994), gender diversity can lead to better social performance. (Veltri et al, 2021; Cucari et al, 2018; Kassinis et al, 2016; Hafsi & Turgut, 2013; Yasser et al, 2017; Xie et al, 2020; Orazanlin and Baydauletov, 2020; Amorelli and Garcia‐Sanchez, 2021; Kyaw et al, 2022; Buertey, 2021; Cuadrado‐Ballesteros et al, 2017; Bernardi et al, 2011; Liu et al, 2020; McGuinness et al, 2017) and better CSR disclosure (Cabeza‐García et al, 2018; Nekhili et al., 2017; Rao & Tilt, 2016).…”
Section: Review Of Related Literaturesmentioning
confidence: 99%
“…It is imperative to discuss the connection between diversity of the board gender and firm performance. Agency theory is used to explain reductions in firm performance and value due to agency costs arises from misalignment of interest between management and shareholders (Finegold et al, 2007; Kyaw et al, 2022). Given that the boards of directors are necessary to reduce agency problems, the characteristics of the board of directors are crucial to enhance its role in harmonizing the interests of shareholders and management (Hillman & Dalziel, 2003; Salleh et al, 2022).…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…In this line, gender diversity increases the board's resource capacity regarding knowledge, values, skills and networks (Konadu et al, 2022). Thus, the presence of women on the board can enrich the resources available in the board's decision-making (Kyaw et al, 2022). Aksoy and Yilmaz (2023) reported that the presence of women on the board reduces the corporate risk for 211 nonfinancial companies listed on Borsa Istanbul during 2016-2020.…”
Section: Board Gender Diversity and Systematic Riskmentioning
confidence: 99%
“…, 2022). Thus, the presence of women on the board can enrich the resources available in the board’s decision-making (Kyaw et al. , 2022).…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%